2010
DOI: 10.1186/1745-6215-11-39
|View full text |Cite
|
Sign up to set email alerts
|

The Health Informatics Trial Enhancement Project (HITE): Using routinely collected primary care data to identify potential participants for a depression trial

Abstract: BackgroundRecruitment to clinical trials can be challenging. We identified anonymous potential participants to an existing pragmatic randomised controlled depression trial to assess the feasibility of using routinely collected data to identify potential trial participants. We discuss the strengths and limitations of this approach, assess its potential value, report challenges and ethical issues encountered.MethodsSwansea University's Health Information Research Unit's Secure Anonymised Information Linkage (SAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…To create the CMD subcohort, we used an algorithm designed to identify cases of patients with CMDs (anxiety and depression), with a sensitivity of 0.32, a specificity of 0.96 and a positive predictive value of 0.74. 45,46 We took the decision to first identify diagnosed individuals because it was necessary to ensure that outcomes were not confounded by treatments prescribed for other reasons. For example, respiratory symptoms related to viral infections are not affected by household conditions.…”
Section: Methodsmentioning
confidence: 99%
“…To create the CMD subcohort, we used an algorithm designed to identify cases of patients with CMDs (anxiety and depression), with a sensitivity of 0.32, a specificity of 0.96 and a positive predictive value of 0.74. 45,46 We took the decision to first identify diagnosed individuals because it was necessary to ensure that outcomes were not confounded by treatments prescribed for other reasons. For example, respiratory symptoms related to viral infections are not affected by household conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that patients with depression can be accurately identified for inclusion in a trial through their primary care records 17. More recently John et al 18 investigated a number of algorithms for identifying adults with CMD using electronic primary care data using the five-item Mental Health Inventory (MHI-5) as a reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of systems have been developed to improve clinical research recruitment using data from electronic health records (EHRs). Proof-of-concept trials have demonstrated that routinely collected primary care data could be used to identify potential participants for a depression trial [10], and a chronic obstructive pulmonary disease (COPD) trial [11] had good sensitivity and specificity. Clinical trial alert systems that drew information from the EHRs have been piloted successfully to identify potential study participants at the point of care [12,13].…”
Section: Introductionmentioning
confidence: 99%